2004
DOI: 10.1016/j.lfs.2004.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Link between free radicals and protein kinase C in glucose-induced alteration of vascular dilation

Abstract: Development of vascular complications in diabetes has been linked to the quality of glucose regulation and characterized by endothelial dysfunction. The exact mechanism behind vascular complications in diabetes is poorly understood. However, alteration of nitric oxide (NO) biosynthesis or bioactivity is strongly implicated and the mechanism behind such alterations is still a subject for research investigations. In the present study, we tested the hypothesis that glucoseinduced attenuation of vascular relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…In this sense, it has been reported that PKC, depending on the tissue analysed, positively (Li et al 1998, Wedgwood et al 2001 or negatively (Mukherjee et al 2001, Yakubu et al 2004 regulates eNOS activity. PKC inhibition has also been reported to increase eNOS activity (Li et al 2005).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this sense, it has been reported that PKC, depending on the tissue analysed, positively (Li et al 1998, Wedgwood et al 2001 or negatively (Mukherjee et al 2001, Yakubu et al 2004 regulates eNOS activity. PKC inhibition has also been reported to increase eNOS activity (Li et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Endothelial NO is formed by eNOS (Förstermann et al 1991, Pollock et al 1991, 1993, which is regulated by multiple kinases (Dinerman et al 1994, Michell et al 2001. Several studies have reported that protein kinase C (PKC) could phosphorylate eNOS and modulate its activity, thereby leading to a decrease (Mukherjee et al 2001, Yakubu et al 2004 or increase (Li et al 1998, Wedgwood et al 2001) of endothelial NO production. In this sense, we observed that male sex hormone deprivation increased PKC activity of rat mesenteric arteries, and this positively modulates neuronal NO release in these arteries (BlancoRivero et al 2005a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In literature there are a number of contrary reports, showing increased relaxations and sensitivity of diabetic aorta to ISO 30) or no signiˆcant eŠect on ISO-induced relaxations. 31) Recently, it has also been reported that b-adrenoceptors induce vascular smooth muscle relaxation by acting through the NO-cGMP pathway and, when that is disrupted by endothelium removal or the presence of an NO synthase inhibitor, the cAMP pathway in smooth muscle is used. 32) To the best of our knowledge, there is no previous data on the eŠects of ALA on ACh-and ISO-induced relaxations in rat aorta.…”
Section: Discussionmentioning
confidence: 99%
“…LPS mediates INOS expression through sequential activation of free radicals, protein kinase C (PKC) and protein tyrosine kinase (PTK) (6). PKC mediates essential cellular signals required for activation, proliferation, differentiation and survival and may be activated through a variety of agonists that may result in free radical generation (27). The GK extract significantly reduced ROS production indicating that the extract is a scavenger or prevents the activation pathway for the generation of ROS.…”
Section: Discussionmentioning
confidence: 99%